Substituição de cimento por isoladores elétricos de porcelana pulverizados na argamassa - Abreu, André (2021)
Due to the growing scarcity of non-renewable natural resources, associated to the fact of the construction industry be one of the biggest consumers, it is necessary to search for new nonconventional materials, which can partially or totally replace raw materials whose extraction and processing cause an important environmental impact. This study aims to investigate the pozzolanic potential of porcelain electrical insulator waste. Therefore, an evaluation of the pozzolanic activity of residues from porcelain electrical insulators was carried out, powdering it and using it as a partial substitute for cement in mortar formulations in the proportions of 5%, 10% and 20%, applying a methodology of adequate processing to explore the pozzolanic activity of the material, meeting the standards for the characterization of cement. The ceramic material, a partial substitute for Portland cement, met the physical and chemical requirements established by the Brazilian standard, in which the sum of SiO2 + Al2O3 + Fe2O3 compounds is greater than 89%, which is higher than the minimum established (70%). The results indicated that this type of material has the potential to replace cement in cementitious mixtures at a level of 5%, being effective in terms of physical and chemical requirements, thus it is possible to conclude that the use of porcelain as a partial replacement for cement can contribute to the reduction of the environmental impact of cementitious mortars with regard to CO2 emissions.